Supply chain collaboration: A game-theoretic approach to profit allocation - Borja Ponte; Isabel Fernández; Rafael Rosillo; José Parre\~no; Nazario García (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: This paper aims to develop a theoretical framework for profit allocation, as a mechanism for aligning incentives, in collaborative supply chains. Design/methodology/approach: The issue of profit distribution is approached from a game-theoretic perspective. We use the nucleolus concept. The framework is illustrated through a numerical example based on the Beer Game scenario. Findings: The nucleolus offers a powerful perspective to tackle this problem, as it takes into consideration the bargaining power of the different echelons. We show that this framework outperforms classical alternatives. Research limitations/implications: The allocation of the overall supply chain profit is analyzed from a static perspective. Considering the dynamic nature of the problem would be an interesting next step. Practical implications: We provide evidence of drawbacks derived from classical solutions to the profit allocation problem. Real-world collaborative supply chains need of robust mechanisms like the one tackled in this work to align incentives from the various actors. Originality/value: Adopting an efficient collaborative solution is a major challenge for supply chains, since it is a wide and complex process that requires an appropriate scheme. Within this framework, profit allocation is essential.
Keywords: 650; beer distribution game; game theory; incentive alignment; profit allocation; supply chain collaboration